1999
DOI: 10.1021/ja981948k
|View full text |Cite
|
Sign up to set email alerts
|

Electron Capture Dissociation of Gaseous Multiply-Charged Proteins Is Favored at Disulfide Bonds and Other Sites of High Hydrogen Atom Affinity

Abstract: Disulfide bonds in gaseous multiply-protonated proteins are preferentially cleaved in the mass spectrometer by low-energy electrons, in sharp contrast to excitation of the ions by photons or low-energy collisions. For S−S cyclized proteins, capture of one electron can break both an S−S bond and a backbone bond in the same ring, or even both disulfide bonds holding two peptide chains together (e.g., insulin), enhancing the sequence information obtainable by tandem mass spectrometry on proteins in trace amounts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

21
688
3
2

Year Published

2000
2000
2005
2005

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 535 publications
(714 citation statements)
references
References 34 publications
21
688
3
2
Order By: Relevance
“…The observed loss of only SH 2 might be explained by either a rearrangement to form a monosulfide bond between the two peptide chains, or by the existence of noncovalent bonding between the chains that might hold them together°after°disulfide°bond°cleavage° [43].°The°dearth of backbone cleavages and the relatively abundant chain ions observed in the reaction product ions of Figure°1°indicate°that°the°disulfide°bonds°are°cleaved preferentially to the backbone bonds upon electron transfer in this reaction. Previous work with ECD has also shown a preference for cleavage of the disulfide bond° [24].…”
Section: Electron Transfer With Dissociationmentioning
confidence: 98%
See 3 more Smart Citations
“…The observed loss of only SH 2 might be explained by either a rearrangement to form a monosulfide bond between the two peptide chains, or by the existence of noncovalent bonding between the chains that might hold them together°after°disulfide°bond°cleavage° [43].°The°dearth of backbone cleavages and the relatively abundant chain ions observed in the reaction product ions of Figure°1°indicate°that°the°disulfide°bonds°are°cleaved preferentially to the backbone bonds upon electron transfer in this reaction. Previous work with ECD has also shown a preference for cleavage of the disulfide bond° [24].…”
Section: Electron Transfer With Dissociationmentioning
confidence: 98%
“…In the ECD work, it was reported that disulfidebound°peptide°chains°cleaved°to°yield°an°odd°electron Chain-S · product, and an even electron Chain-SH product° [24].°The°work°with°ECD°also°reports°that°the°even electron Chain-SH product tends to come from the more highly charged chain, presumably due to polarization of the SOS bond. It has been proposed that this occurs when a hydrogen atom (H · ), generated by electron capture at a protonation site, attacks one of the sulfur atoms, leading to cleavage of the disulfide bond.…”
Section: Electron Transfer With Dissociationmentioning
confidence: 99%
See 2 more Smart Citations
“…54 This mechanism can be particularly useful for explanation of the cleavage of disulfide bonds. 54,57 Numerous experimental facts have indicated that the cleavage of the peptide backbone has low specificity and fragmentation of strong bonds can appear in the presence of weak bonds. This non-specific nature of ECD has been explained in terms of the non-ergodicity.…”
Section: Electron Capture Dissociation Mechanismmentioning
confidence: 99%